Polynomials and high-dimensional spheres. (October 2019) - Peterson, Amy; Sengupta, Ambar N.
Abstract: We show that a natural class of orthogonal polynomials on large spheres in N dimensions tend to Hermite polynomials in the large-N limit. We determine the behavior of the spherical Laplacian as well as zonal harmonic polynomials in the large-N limit.